Low-to-Moderate Alcohol Consumption is Associated With Hippocampal Volume in Fibromyalgia and Insomnia. Issue 6 (2nd November 2017) - Boissoneault, Jeff; Vatthauer, Karlyn; O'Shea, Andrew; Craggs, Jason G.; Robinson, Michael; Staud, Roland; Berry, Richard B.; Perlstein, William; Waxenberg, Lori; McCrae, Christina S.
Abstract : Fibromyalgia and chronic insomnia are frequently comorbid conditions with heightened sensitivity to painful stimuli, potentially subserved by the hippocampus. Recent evidence suggests moderate alcohol consumption is associated with reduced fibromyalgia symptom severity. We examined the relationship among alcohol use, hippocampal morphology, fibromyalgia, and insomnia symptom severity in 41 fibromyalgia patients (19 with insomnia). A 14-day diary of sleep, pain, and alcohol consumption was followed by structural MRI. Analyses indicated greater bilateral hippocampal volume, lower clinical pain intensity, and better sleep quality in moderate drinkers versus abstainers. Underlying mechanisms may include gamma-amino butyric acid (GABA) receptor agonism, n-methyl d-aspartate (NMDA) receptor antagonism, and psychosocial factors. Further study of the relationship between alcohol use and fibromyalgia and insomnia symptom severity is warranted.